Maternal immune and affiliative biomarkers and sensitive parenting mediate the effects of chronic early trauma on child anxiety. Issue 6 (11th September 2017) - Ulmer-Yaniv, A.; Djalovski, A.; Yirmiya, K.; Halevi, G.; Zagoory-Sharon, O.; Feldman, R.
Abstract : Background: Chronic early trauma alters children's stress reactivity and increases the prevalence of anxiety disorders; yet the neuroendocrine and immune mechanisms underpinning this effect are not fully clear. Animal studies indicate that the mother's physiology and behavior mediate offspring stress in a system-specific manner, but few studies tested this external-regulatory maternal role in human children exposed to chronic stress. Methods: We followed a unique cohort of children exposed to continuous wartime trauma ( N = 177; exposed; N = 101, controls; N = 76). At 10 years, maternal and child's salivary immunoglobulin A (s-IgA) and oxytocin (OT), biomarkers of the immune and affiliation systems, were assayed, maternal and child relational behaviors observed, mother and child underwent psychiatric diagnosis, and child anxiety symptoms assessed. Results: War-exposed mothers had higher s-IgA, lower OT, more anxiety symptoms, and their parenting was characterized by reduced sensitivity. Exposed children showed higher s-IgA, more anxiety disorders and post traumatic stress disorder, and more anxiety symptoms. Path analysis model defined three pathways by which maternal physiology and behavior impacted child anxiety; (a) increasing maternal s-IgA, which led to increased child s-IgA, augmenting child anxiety; (b) reducing maternal OT, which linked with diminished child OT and social repertoire; and (c) increasing maternal anxiety, which directly impacted child anxiety. Conclusions: Our findings, the first to measure immune and affiliation biomarkers in mothers and children, detail their unique and joint effects on children's anxiety in response to stress; highlight the relations between chronic stress, immune activation, and anxiety in children; and describe how processes of biobehavioral synchrony shape children's long-term adaptation.